Short‐term outcomes following implementation of a dedicated young adult congenital heart disease transition program. (20th November 2017) - Vaikunth, Sumeet S.; Williams, Roberta G.; Uzunyan, Merujan Y.; Tun, Han; Barton, Cheryl; Chang, Philip M.
Abstract: Objective: Transition from pediatric to adult care is a critical time for patients with congenital heart disease. Lapses in care can lead to poor outcomes, including increased mortality. Formal transition clinics have been implemented to improve success of transferring care from pediatric to adult providers; however, data regarding outcomes remain limited. We sought to evaluate outcomes of transfer within a dedicated transition clinic for young adult patients with congenital heart disease. Design, Setting, and Patients: We performed a retrospective analysis of all 73 patients seen in a dedicated young adult congenital heart disease transition clinic from January 2012 to December 2015 within a single academic institution that delivered pediatric and adult care at separate children's and adult hospitals, respectively. Intervention and Outcome Measures: Demographic characteristics including congenital heart disease severity, gender, age, presence of comorbidities, presence of cardiac implantable electronic devices, and type of insurance were correlated to success of transfer. Rate of successful transfer was evaluated, and multivariate analysis was performed to determine which demographic variables were favorably associated with transfer. Results: Thirty‐nine percent of patients successfully transferred from pediatric to adult services during the study period. Severe congenital heart disease (OR 4.44, 95% CI 1.25‐15.79, P  = .02) and presence of a cardiac implantable electronic device (OR 4.93, 95% CI 1.18‐20.58, P  = .03) correlated with transfer. Trends favoring successful transfer with presence of comorbidities and private insurance were also noted. Conclusions: Despite a dedicated transition clinic, successful transfer rates remained relatively low though comparable to previously published rates. Severity of disease and presence of implantable devices correlated with successful transfer. Other obstacles to transfer remain and require combined efforts from pediatric and adult care systems, insurance carriers, and policy makers to improve transfer outcomes.